Geometria em Movimento: Arduino e Robótica no Ensino de Matemática - DONIZETH JACINTO DE SOUZA (2024)
This work investigates the integration of educational technologies, such as Arduino and robotics, in teaching plane geometry to 9th grade elementary school students. The abstraction of geometric concepts often results in difficulties in understanding and lack of motivation. To address this challenge, this study proposes an approach that uses rapid prototyping platforms to facilitate practical application. The specific objectives are to develop a activities using Arduino and robotics to teach geometry concepts, promote interdisciplinary learning by integrating knowledge of mathematics, robotics, and train teachers to use these technologies in the classroom. The methodology includes the creation of activities that involve assembling robots and programming geometric tasks.